Research on enhanced absorption technology of odour pollution. Issue 5 (May 2021) - Deng, Gaoya; Zeng, Wenhao; Chen, Dingsheng; Zeng, Huanmu; Huang, Jianhang; Chen, Zhihang; Cen, Chaoping
Abstract: The Odor pollution problem in the feed industry was particularly prominent, which restricts the development of the industry and threatens the "vegetable basket" livelihood project. The air pollutant emission of feed processing enterprises were investigated in Pearl River Delta and its surrounding areas, find out the peculiar odor pollutants in feed industry through analysis and monitoring. With the characteristics of many kinds of odor pollutants and low threshold in feed industry, high efficient adsorbent was developed to explore the influence of adsorbent concentration, residence time, temperature and space velocity on the purification efficiency of odor gas, so as to achieve more efficient coordination of odor VOCs pollutants. In this study, a highly effective SCOP adsorbent was developed, and the removal rate of the main odor pollutants was more than 90%. It provides technical support for air pollution control and government environmental management of feed industry.